2004
DOI: 10.1088/0022-3727/37/14/010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of halogen containing radicals in silicon etching plasmas and density measurement by UV broad band absorption spectroscopy

Abstract: Silicon etching by-products play a major role in silicon gate etching processes because they are the precursors to SiOClX passivation layer formation on feature sidewalls and on reactor walls. As a result, the understanding and modelling of these processes relies on the knowledge of the absolute value of SiClX (SiBrX) fluxes to the surfaces exposed to the plasma. However, only a few experimental data on the absolute concentration of SiClX etch byproducts are available in the literature. In this work, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 50 publications
(73 reference statements)
1
78
0
Order By: Relevance
“…Previous studies have found this type of structure for cations of fluorinated and chlorinated silanes [29,85] and germanes [23]. The non-classical structures are lower in energy than the classical ones except for [SiH 3 Br] + and [SiH 2 Br 2 ] + . It is again difficult to measure the adiabatic IE a s to the non-classical cations.…”
Section: Ionization Energies Of Sih X X Y and Potential Energy Surfacmentioning
confidence: 70%
See 3 more Smart Citations
“…Previous studies have found this type of structure for cations of fluorinated and chlorinated silanes [29,85] and germanes [23]. The non-classical structures are lower in energy than the classical ones except for [SiH 3 Br] + and [SiH 2 Br 2 ] + . It is again difficult to measure the adiabatic IE a s to the non-classical cations.…”
Section: Ionization Energies Of Sih X X Y and Potential Energy Surfacmentioning
confidence: 70%
“…6). Ion complexes SiHF + -H 2 , SiH 2 + -FH, SiHCl + -H 2 , and SiH 2 + -ClH are lower in energy than their classical ones, while the three [SiH 3 Br] + structures are within 7 kJ/mol. Photoelectron spectroscopic studies have obtained vertical IEs of 11.61-11.65 eV and 10.96-11.03 eV for SiH 3 Cl and SiH 3 Br [86][87][88][89].…”
Section: Ionization Energies Of Sih X X Y and Potential Energy Surfacmentioning
confidence: 89%
See 2 more Smart Citations
“…46,47 In fact, the population transfer between the a 3 D ͑3d 9 4s 1 configuration͒ and a 3 F ͑3d 8 4s 2 configuration͒ manifolds by collision with Ar atoms in the plasma is expected to be very small because rare-gas collisions are very inefficient for transferring an electron from a 3d shell to a 4s shell. For example, in a Cu hollow cathode discharge with ϳ1 Torr Ar carrier gas, the ratio of the Cu 2 D metastable state ͑3d 9 4s 2 ͒ to the ground state 2 S ͑3d 10 4s 1 ͒ was much higher than that measured in a Cu thermal evaporation.…”
Section: Optical Absorption Measurementsmentioning
confidence: 99%